2022
DOI: 10.3389/fmicb.2022.927889
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Solubilizing Pseudomonas sp. Strain WS32 Rhizosphere Colonization-Induced Expression Changes in Wheat Roots

Abstract: Rhizosphere colonization is a pre-requisite for the favorable application of plant growth-promoting rhizobacteria (PGPR). Exchange and mutual recognition of signaling molecules occur frequently between plants and microbes. Here, the luciferase luxAB gene was electrotransformed into the phosphate-solubilizing strain Pseudomonas sp. WS32, a type of plant growth-promoting rhizobacterium with specific affinity for wheat. A labeled WS32 strain (WS32-L) was applied to determine the temporal and spatial traits of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Despite the similar colonization potential of the two wheat cultivars observed for SBW25 WT and Δ viscA , respectively, SBW25 WT was found to also impact plant root architecture parameters dependent on plant genotype. It has previously been shown that inoculation of plants with plant-beneficial bacteria alters root morphology ( 66 68 ), but to our knowledge, this is the first time that it is shown to be cultivar-dependent. The observed differential effect on plant root parameters could be the result of differential community assembly, dependent both on plant genotype and/or the ability of the inoculant to produce viscosin.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the similar colonization potential of the two wheat cultivars observed for SBW25 WT and Δ viscA , respectively, SBW25 WT was found to also impact plant root architecture parameters dependent on plant genotype. It has previously been shown that inoculation of plants with plant-beneficial bacteria alters root morphology ( 66 68 ), but to our knowledge, this is the first time that it is shown to be cultivar-dependent. The observed differential effect on plant root parameters could be the result of differential community assembly, dependent both on plant genotype and/or the ability of the inoculant to produce viscosin.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the similar colonization potential of the two wheat cultivars observed for SBW25 and ∆viscA, respectively, viscosin was found to impact plant root architecture parameters dependent on plant genotype. It has previously been shown that inoculation of plants with plant beneficial bacteria alters root colonization [57,58,59], but to our knowledge this is the first time, that is has been shown to be cultivar-dependent. The observed differential effect on plant root parameters could be the result of differential community assembly, dependent both on plant genotype and/or the ability of the inoculant to produce viscosin.…”
Section: Discussionmentioning
confidence: 81%